SISTEM INFORMASI GEOGRAFIS PEMETAAN DAN PENENTUAN LOKASI WISATA ALAM STRATEGIS DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Rizal Tjut Adek; Zara Yunizar; Mahendra Febriliansyah (P3M Politeknik Negeri Banjarmasin, 2023)
Langkat is one of the districts in North Sumatra which has a variety of good tourist sites to visit. Some of the tourists still don't know geographically the tourist objects visited. This study aims to create an information system for mapping and determining the location of strategic tourist objects in Langkat Regency using the Simple Additive Weighting (SAW) method. The system that will be created will recommend places that have the potential to be selected as tourist spots. Determining strategic tourist objects using a weighting process with fuzzy logic is then calculated by implementing the SAW method and considering a number of criteria, namely the average number of visits to the tour, the distance traveled from the capital of Langkat Regency to the tourist attraction, the price of admission to the object tourism and the completeness of facilities and infrastructure at these tourist objects. Of the 34 total data, the ranking results for each filter applied are different. The filters applied are visits, distance, costs, and facilities. In all existing filters, the Bukit Lawang tourist attraction is always ranked first